Pengembangan Modul Ajar Matematika Berbasis Nilai-Nilai Budaya Bugis Terintegrasi Dimensi Profil Pelajar Pancasila - Fitriani A, Fitriani A; Baharuddin, Muhammad Rusli; Yanti, Rosmalah; Erni, Erni (Jurnal Studi Guru dan Pembelajaran, 2024)
The very urgent problems facing the world of education are (a) the availability of teaching modules that maintain a balance between intellectual intelligence and character, (b) the fragmentation of local cultural values ​​with foreign culture which has the impact of eliminating the culture of good manners or etiquette, and (c) The results of the education report evaluation show that national education goals have not been achieved. This research approach uses Development Research (R&D) with research implementation stages following the Four D Model (4D) which consists of four development stages, namely: Define, Design, Develop, and Disseminate. The Define stage includes literature study activities and field surveys for the purposes of problem identification and need analysis, the Design stage includes initial product design activities, the Develop stage includes expert validation activities, product revisions, one-on-one and small group trials, and the Disseminate stage includes socialization activities fieldwork and final product revisions. The novelty offered in this research is a teaching module that integrates the cultural values ​​of the Bugis tribe (Sipakatau, Sipakalebbi, and Sipakainge) with the goals of national education or the dimensions of the Pancasila student profile.